Synthesis and Structure of [(PPh2=E)2C=Mg]2 (E = S, NSiMe3) : novel magnesium carbene complexes. - Foo, Ming Choo. (2009)
Novel magnesium bis(diphenylphosphorano)methaniide complexes have been synthesized and characterized. Reaction of [Ph2PCH2PPh2] with sulphur afforded the ligand [CH2(PPh2=S)2] (1). Treatment of 1 with Mg(nBu)2 gave the first example of magnesium bis(diphenylthiophosphorano)methaniide complex [(PPh2=S)2C=Mg]2 (2). Reaction of [Ph2PCH2PPh2] with azidotrimethylsilane afforded the ligand [CH2(PPh2=NSiMe3)2] (3). Treatment of 3 with Mg(nBu)2 gave novel [(PPh2=NSiMe3)2C=Mg]2 (4). X-ray structure analyses of 2 and 4 confirmed that the two magnesium carbene moieties [(PPh2=S)2C=Mg] in 2 dimerized in a head-to-head manner while the two magnesium carbene moieties [(PPh2=NSiMe3)2C=Mg] in 4 dimerized in a head-to-tail manner. The synthesis of 2 and 4 are highly significant as they demonstrate the existence of C=Mg double bond.